Primary orofacial granulomatous involvement of lip and gingiva only: A diagnostic challenge - Shweta Bansal; Arun Garg; Richa Khurana; Archisha Bansal (Wolters Kluwer Medknow Publications, 2020)
Wiesenfeld described orofacial granulomatosis (OFG) as a group of noncaseating granulomatous disorders affecting the different parts of the body including oral and maxillofacial region, which can have variable etiology. The involvement of oral and maxillofacial region can be exclusive or primary before the involvement of other organs. OFG is a multifactorial clinicopathologic disorder, and its clinical manifestation mimics the various systemic conditions making its diagnosis tough for a dentist. Delay in diagnosis and evaluation of OFG may cause indurated, swollen lips that may compromise cosmetic face value, speaking, and eating functions, and other possible systemic granulomatous disorders can be missed. Here, we present a case of OFG with tooth-associated infection without any recognizable systemic cause. This article presents the diagnostic challenges that a dentist may face in diagnosing such cases, and thus treatment planning should be of the multidisciplinary approach. Regular follow-up is very essential for proper care and management.